Lanthanum titanate nanometric powder: An investigation on synthesis by solid state route. (2020) - Vignesh Babu, S.; Vivian Inbanayagam, S.; Ananda Rao, M.; Kumaresh Babu, S.P.; Srinivasan, S.A.
Abstract: La2 Ti2 O7 nano metric powder was prepared using solid state route and evaluated in the present study. Precursors of lanthanum oxide and titanium dioxide were blended, synthesized at 850 °C for 8 h. The phase analysis of the synthesized powder was carried out using XRD diffraction analysis to check the purity of the perovskite La2 Ti2 O7 compound formed. The crystalline size measurement was carried out using Debye–Scherrer formula which reveals that the synthesized powder at 850 °C for 8 h is in the range of 49.54 nm. The powder morphology was studied using the SEM and EDS result confirms the presence of La, Ti and O elements. The SEM results reveal irregular morphology of the powders and few clusters which may be attributed to the presence of the moisture in them.